Peningkatan Literasi Kebencanaan pada Masa Tanggap Darurat Bencana pada Mahasiswa Manajemen Bencana Melalui Kunjungan Ilmiah ke Human Initiative Headquarter Depok - Hayatul Khairul Rahmat; Fathin Aulia Rahman; Didik Hariyadi Raharjo; H Hasrian; Ahmad Aldizar Akbar (Yayasan REDI Tiga Monas, 2023)
Indonesia is a country that is prone to natural disasters caused by Indonesia's position at the meeting point of three active world plates, namely Indo-Australian, Eurasian and Pacific. Therefore, it is important to make efforts to reduce disaster risk or disaster preparedness, one of which is for students. This community service activity aims to increase disaster literacy among disaster management students, especially during the emergency response period, through a scientific visit to the Human Initiative Headquarters Depok. The hope is that students will become an intelligent part of society who will later disseminate information related to disaster literacy, especially during the disaster emergency response period. This activity is carried out in three stages, namely the preparation stage, implementation stage and evaluation stage. Analysis of students who attended and participated in these activities were able to receive and digest the material from the socialization provided and then there was an increase in student disaster literacy, especially during the emergency response period.